2014
DOI: 10.1002/cad.20070
|View full text |Cite
|
Sign up to set email alerts
|

Some Long-Standing and Emerging Research Lines in Africa

Abstract: Early research on child development in Africa was dominated by expatriates and was primarily addressed to the topics of testing the cross-cultural validity of theories developed "in the West," and the search for universals. After a brief review of the outcome of that research, we propose two additional types of motivation that seem important to us as African researchers begin to take the lead in articulating research agendas for the study of child development in Africa: articulating the contextual relevance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Although this work will take time, there is no substitute for careful test development work when assessing children growing up in non-Western contexts (Matafwali & Serpell, 2014). Although as researchers we understand the reasons why some investigators would choose an existing assessment as a means of getting to the results as quickly as possible, we reject the underlying belief that children can be tested in the same way anywhere in the world, and that the resulting data will be directly comparable (Henrich et al, 2010; Matafwali & Serpell, 2014; Serpell & Haynes, 2004; Serpell & Marfo, 2014). Western assessments may indeed be acceptable for use in a broad range of contexts, but careful psychometric analyses and norming are necessary precursors to the use of these assessments in an evaluative sense.…”
Section: Discussionmentioning
confidence: 89%
“…Although this work will take time, there is no substitute for careful test development work when assessing children growing up in non-Western contexts (Matafwali & Serpell, 2014). Although as researchers we understand the reasons why some investigators would choose an existing assessment as a means of getting to the results as quickly as possible, we reject the underlying belief that children can be tested in the same way anywhere in the world, and that the resulting data will be directly comparable (Henrich et al, 2010; Matafwali & Serpell, 2014; Serpell & Haynes, 2004; Serpell & Marfo, 2014). Western assessments may indeed be acceptable for use in a broad range of contexts, but careful psychometric analyses and norming are necessary precursors to the use of these assessments in an evaluative sense.…”
Section: Discussionmentioning
confidence: 89%
“…Researchers exploring child development in SSA have identified that the primary care of children is often shared beyond the biological parents (Serpell and Marfo, 2014a, Serpell and Marfo, 2014b, Pence and Nsamenang, 2008). To some extent our findings support this, with mothers’ noting that grandmothers, aunties, older siblings, and to a lesser extent, fathers, all play some role in child care.…”
Section: Discussionmentioning
confidence: 99%
“…When doing cross-cultural research, Syed (2020) also encourages researchers to look at mixed methods research and dynamic mediators (a methodology) to ensure rigorous and considerate comparisons. Ensuring that our findings are communicated in an accessible and direct way to the public, as suggested by Serpell and Marfo (2014), might also ensure our research has relevance to communities and professionals outside what is reported by Western media.…”
Section: Future Recommendationsmentioning
confidence: 99%